A new kannemeyeriiform dicynodont (Ufudocyclops mukanelai, gen. et sp. nov.) from Subzone C of the Cynognathus Assemblage Zone, Triassic of South Africa, with implications for biostratigraphic correlation with other African Triassic faunas. Issue 2 (4th March 2019) - Kammerer, Christian F.; Viglietti, Pia A.; Hancox, P. John; Butler, Richard J.; Choiniere, Jonah N.
ABSTRACT: A new taxon of kannemeyeriiform dicynodont, Ufudocyclops mukanelai, is described based on a well-preserved skull from Subzone C of the Cynognathus Assemblage Zone, which are the youngest strata (probably Middle Triassic) of the Beaufort Group (uppermost Burgersdorp Formation) in South Africa. Ufudocyclops mukanelai is diagnosed by its autapomorphic intertemporal morphology: the intertemporal bar in this taxon is 'X'-shaped—broad anteriorly and posteriorly but distinctly 'pinched' at mid-length and bears a deep, triangular depression immediately behind the enormous pineal foramen. The new kannemeyeriiform can also be diagnosed by the presence of a laterally expanded jugal plate beneath the orbit, and highly discrete, ovoid nasal bosses separated by a broad, unornamented median portion of the premaxilla and the nasals. Two partial dicynodont skulls from this subzone, previously identified as specimens of the otherwise Tanzanian taxon Angonisaurus, are also referable to U . mukanelai . Removal of these specimens from the hypodigm of Angonisaurus eliminates a crucial point of correlation between Cynognathus Subzone C and the Manda Beds of Tanzania and suggests that Subzone C preserves a distinct, endemic fauna, not just a southern extension of the better-known Middle–Late Triassic tetrapod faunas from Tanzania and Zambia. Inclusion of Ufudocyclops in a phylogenetic analysis of anomodonts recovers it as an early stahleckeriid, the first record of this clade from the Cynognathus Assemblage Zone.